Effects of chronic bubble tea administration on behavior and cognition in C57BL/6 mice - Yao, Yitan; Shi, Shengya; Yang, Yating; Luo, Bei; Li, Mengdie; Zhang, Ling; Yuan, Xiaoping; Liu, Huanzhong; Zhang, Kai (Frontiers in Psychiatry, 2022)
Purpose: There is a lack of rigorous experimental evidence to verify the effects of bubble tea on body weight and mental health, especially whether it is an addictive thing. Methods: Male adult C57BL/6 mice were randomly assigned to two groups, including the bubble-tea and the control group. The change in their body weight was calculated. Behavior tests include novel object recognition test (NORT), elevated plus maze test (EPMT), forced swim test (FST), tail suspension test (TST), conditioned place preference (CPP). Results: There was a significant time effect on weight change of the two groups (F=36.83, P<0.01). The bubble tea-treated mice spent significantly less time in the open arms, indicating an increase in anxiety (t=2.39, P=0.03). In FST, bubble tea treatment produced a significantly increased immobility time (186.58±29.67s) as compared to pure water treated group (112.50±46.67s) (t=-3.79, P<0.01). Similarly, the immobility time in the TST was also significantly increased by bubble tea treatment (437.63±27.72 s) compared to the treatment with pure water (340.24±77.22s) (t=-3.36, P<0.01). We investigated the rewarding effects of bubble tea, using the CPP paradigm, which measures the rewarding properties of abused drugs. Independent-samples t-test revealed no significant difference between the two groups (t=-0.47, P=0.65). Conclusion: In conclusion, we showed that long-term administration of bubble tea could not induce addictive behavior in mice. Meanwhile, the long-term effects of bubble tea on weight were also very limited. However, long-term consumption of bubble tea can lead to anxiety and depression-like behaviors and impair cognitive function in mice.